Gravimetric measurements in Tanzania in the framework of the ANR CoLiBrEA project - (:unkn) unknown (My University, 2013)
The picture shows the gravimetric measurements made in Tanzania, in the framework of the ANR CoLiBrEA project. CoLiBrEA is a multidisciplinary project that aims to understand the processes involved in the continental break-up of the lithosphere in East Africa. The study focuses on the only place on the continent where the earliest stage of rifting is currently occurring and where the magma - tectonic interaction can be observed in action. The project started in 2012, with collaboration between French, American and Tanzanian institutions, and focuses on the Tanzanian Northern Divergence. The instruments used for these measurements were Scintrex CG5, which are part of the GMob (Mobile Gravity National Park of Résif) network. Data from these measurements are distributed by Résif, a national research infrastructure dedicated to the observation and understanding of the Earth's internal structure and dynamics. Résif is based on high-tech observation networks composed of seismological, geodetic and gravimetric instruments that are densely deployed throughout France and during campaigns abroad in areas of high scientific interest. The data collected enable the study of ground deformation, surface and deep structures, local and global seismicity and natural hazards, particularly seismic, on French territory with a high spatio-temporal resolution. Résif is integrated into the European (EPOS - European Plate Observing System) and worldwide systems of instruments used to image the interior of the Earth as a whole and to study numerous natural phenomena.
Keywords: African Research